Assessing the Risk, Bioavailability, and Phytoremediation of Heavy Metals in Agricultural Soils: Implications for Crop Safety and Human Health - Ullah, Qudrat; Aqsa; Ishaq, Ayesha; Mumtaz, Ayesha; Fatima, Farzeen; Mehwish, Saba; Ghaffar, Aisha; Bibi, Ruqia (Indonesian Journal of Agriculture and Environmental Analytics, 2024)
This review addresses heavy metal contamination in agricultural soils, focusing on bioavailability, toxicity, and phytoremediation techniques. We identify significant regional variations in cadmium and lead levels, posing health risks through crop consumption. Effective phytoremediation methods, such as phytoextraction and Phytostabilization, have shown marked improvements over recent years. Recommendations include best practices for soil management, stringent regulatory measures, and advanced research in biotechnological remediation methods. This study underscores the urgent need for integrated strategies to ensure food safety and sustainable agriculture in sector.